KEBERADAAN PRINSIP (MAQASHID AL-SYARIAH) HIFDZUL MAL DALAM KEGIATAN INVESTASI KONVENSIONAL NON MAISIR - suharsono, suharsono; Aini, Kuratul; Irbah, Ariq Nurjannah (Investama : Jurnal Ekonomi dan Bisnis, 2023)
This scientific article will review in depth about The existence of the principle of maqashidusya'riah, namely hifdzul mal (safeguarding property) in conventional non-maisir investment practices, Maqashidusya'riah as the main foundation of syariah principles in various muamalah activities of Muslims today has been packaged in such a way, Thus creating a stigma in people's understanding that a service product that does not dissolve itself as a syariah based product is understood as incompatible with Islamic principles. The principle of maqashidusya'riah may not only exist in products that have syariah license but also exist in conventional products that have developed to date Based on a review of several studies and relevant articles, the results were found that: If a conventional investment service product in terms of services has prioritized transparency over the progress of related shares as well as possible without any element of manipulation or gharar (fraud), Also, investment activities in the world of capital markets are carried out properly according to the limits in Islam so that it is in accordance with the principles of hifdz al-mal in maqashidussyari'ah.